Literary-Cartographic Models in the Corpus of Czech Prose - Richard Změlík (Colloquia Humanistica)
The study focuses on problems of literary cartography. Part one deals with basic issues such as the definition of the discipline and attempts to define its basic taxonomy, and also presents selected literary-cartographic projects. Part two presents literary-cartographic models that are part of the literary corpora of Czech prose. Specifically, it deals with models of the fictional topography of Prague in the work of selected Czech writers. The aim is not only to demonstrate what such models look like, but, above all, to present a way of working with them in the process of literary interpretation.